2007
DOI: 10.1177/039463200702000414
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Numb Immunoreactivity in Salivary Gland Carcinomas

Abstract: The gene numb encodes for a protein (Numb) involved in cell fate decisions in Drosophila, with proposed endocytic and developmental functions in mammalians. The distribution pattern of Numb in human tissues however, has not been fully characterized. We set out to explore the immunohistochemical expression of Numb in normal and neoplastic (28 adenoid cystic and 34 mucoepidermoid carcinomas) salivary glands, and correlated the results with the clinico-pathologic features of the neoplasms. Intense Numb immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…This suggests that loss of Numb expression is involved in the formation and development of epithelioid MPM. Negative Numb immunohistochemistry with poor prognosis was previously reported in human salivary gland carcinomas and breast tumors (12,24). Our data also showed that the reduction in Numb expression was associated with poor long term outcome in epithelioid MPM patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that loss of Numb expression is involved in the formation and development of epithelioid MPM. Negative Numb immunohistochemistry with poor prognosis was previously reported in human salivary gland carcinomas and breast tumors (12,24). Our data also showed that the reduction in Numb expression was associated with poor long term outcome in epithelioid MPM patients.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, in vivo RNA interference of Numb in a model of mouse lymphomagenesis was found to accelerate the onset of lymphomas (23). Loss of Numb expression has also been reported in some types of human cancers, such as breast cancers, non-small cell lung carcinomas, salivary gland carcinomas and medulloblastomas (20,21,24,25). In human astrocytomas, there is a trend of higher Numb expression in more malignant tumors (26).…”
Section: Introductionmentioning
confidence: 91%
“…The relationship between NUMB and tumorigenesis was discovered in recent studies [12, 13] and accumulating evidence suggests a potential tumor suppressor role for NUMB, including stabilization of p53 [14, 15] and inhibition of Notch signaling [16, 17]. Indeed, these proposed tumor suppressive functions of NUMB are consistent with previous studies conducted in breast cancer [18], non-small cell lung cancer (NSCLC) [19], and salivary gland carcinomas [20] in which tumors exhibited reduced expression of NUMB. On the other hand, overexpression of NUMB was found in astrocytomas [21] and cervical squamous carcinoma cells [22], suggesting that NUMB also possesses oncogenic potential.…”
Section: Introductionsupporting
confidence: 78%
“…149 Loss of NUMB is associated with tumour aggressiveness and BRCA1 status in patients with breast cancer, 150 and poor prognosis in patients with salivary gland carcinomas. 151 …”
Section: Discussionmentioning
confidence: 99%